The Role of Knowledge Management in Reducing Administrative Corruption A Field Study on Ministry of Commerce in Jeddah (Governorate) - Bukhari, Abraa Ismail; Gheith, Nirvana Abdelrahman (Journal of Economic, Administrative and Legal Sciences, 2022)
This study examines the role of organizations adopting knowledge management with its various processes of generation, storage, distribution and application of knowledge to counter the spread of the phenomenon of administrative corruption. The importance of this study is its modernity, as this is the first study that examines the role of knowledge management in reducing administrative corruption, and a statement was obtained from the King Fahd National Library, and it is possible to benefit from it as a reliable nucleus in building modern studies related to the study variables. The study will also provide a large amount of information on the role of using the dimensions of knowledge management in reducing administrative corruption in the Ministry of Commerce in the Kingdom of Saudi Arabia. The study aims to identify the role of knowledge management in its various dimensions in reducing administrative corruption at the Ministry of Commerce in Jeddah Governorate. The study seeks to answer several questions about what is the role of knowledge management in reducing administrative corruption according to the point of view of the administrative staff in the Ministry of Commerce in Jeddah, and what is the level of application of knowledge management with its dimensions (knowledge generation, knowledge storage, knowledge distribution, knowledge application) in the Ministry of Commerce In Jeddah, and what is the effect of personal variables (age, educational level, years of experience) on the study variables (knowledge management, administrative corruption). The study relied on the descriptive analytical approach; The questionnaire was also used as a data collection tool. The study was applied to a sample of (203) administrative employees in the Ministry of Commerce in Jeddah. The data were treated statistically using the Statistical Package for Social Sciences (SPSS) program, and the study reached several results, the most important of which are: Knowledge management is widely applied in the Ministry of Commerce in Jeddah with a relative weight of (81%) and a high level of application of mechanisms to reduce administrative corruption in the Ministry of Commerce In Jeddah, at a relative weight of (79.8%), the study came out with a set of recommendations, including the need to use practical means by the Ministry of Commerce to encourage employees to put forward new ideas and indicate the importance of holding periodic meetings with its employees in order to educate them about their rights and duties.
Keywords: Knowledge Management; Administrative Corruption; The Ministry of Commerce